Case Reports in Oncological Medicine Myoepithelioma: A New Rearrangement Involving the LPP Locus in a Case of Multiple Bone and Soft Tissue Lesions - Géraldine Pairet; Gaëlle Tilman; Rafaël Sciot; Thomas Schubert; Vasiliki Perlepe; Hélène A. Poirel; Christine Galant (Case Reports in Oncological Medicine)
We report a case of multiple myoepithelioma with synchronous bone and soft tissue tumors, associated with a new genomic alteration of the LPP locus. The lesions occurred in the foot by presenting one lump in the plantar soft tissue, and three lesions were detected in the calcaneus and in the navicular bone. All tumors showed the double immunophenotype of epithelial markers and S100 protein expression. No rearrangement of the EWSR1 and FUS loci was detected as reported in myoepitheliomas. However, molecular karyotyping detected an unbalanced rearrangement of the LPP locus, not involving the HMGA2 locus, which is the most frequent translocation partner observed in benign mesenchymal tumors such as lipomas (of soft tissue as well as parosteal) and pulmonary chondroid hamartoma.